Parent-child concordance on the Pubertal Development Scale in typically developing and autistic youth. (September 2020) - Clawson, Ann; Strang, John F.; Wallace, Gregory L.; Gomez-Lobo, Veronica; Jack, Allison; Webb, Sara J.; Pelphrey, Kevin A.; ,
Highlights: We compared parent and youth Pubertal Development Scale (PDS) responses in autistic and typically developing (TD) youth. There were no differences in parent-youth agreement between autistic and TD youth for overall ratings of puberty. Autistic males and their parents differed on item-level responses and when rating physical signs of hormonal processes. The PDS may be a useful measure in autism for understanding youth and parent perceptions of pubertal progression. Abstract: Background: Characterizing puberty in autism spectrum disorder (ASD) is critical given the direct impacts of pubertal progression on neural, cognitive, and physical maturation. Limited information is available about the utility and parent-child concordance of the self-report and parent-report Pubertal Development Scale (PDS) in ASD, an economical and easily administered measure. Method: The primary aim of this study was to examine the concordance between self-report and parent-report PDS ratings in autistic males and females ages 8–17y compared to typically developing (TD) youth, including using the PDS to derive informant-based estimates of adrenal and gonadal development. We hypothesized that there would be greater parent-youth discrepancies in pubertal ratings among autistic males. Our second aim was exploratory; we examined whether individual characteristics impact PDS concordance and hypothesized that lower intellectual and adaptive skills, higher autistic traits, and reduced self-awareness/monitoring would correlate with lower concordance. Results: There were no significant diagnostic group differences in parent-youth concordance for overall PDS scores among males and females. Autistic males had significantly lower inter-item agreement with their parents than TD males and had lower agreement for both adrenal and gonadal aspects of pubertal maturation (adrenal κ = .48; gonadal κ = .55). Conclusions: The PDS is a feasible measure in ASD. Greater parent-youth discrepancies in autistic males may be due to reduced parental awareness or reduced insight into pubertal maturation among autistic males. Future research is needed to further elucidate individual and/or environmental characteristics that influence youth- and parent-reported PDS scores, including differences in self-perception and insight.